A VLBI polarisation study of 43 GHZ SiO masers towards VY CMA - Richter, Laura (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2006)
This thesis reports the calibration, imaging and analysis of one epoch of VLBI observations of the v (italics) = J (italics) = 1-0 transition of SiO towards VY CMa. Full polarisation information was recorded, allowing high resolution synthesis maps of each of the four Stokes parameters to be produced. A total of 81 maser components were extracted from the total intensity map, each approximately 1 mas in size. The emission spans approximately 100 x 80 mas in right ascension and declination and is concentrated to the east. The maser component positions were fitted to a ring of radius ~ 3.2Râ‚Š (italics), or 7.2 x 1OÂ¹â ´ cm for a stellar distance of 1.5 kpc. If the stellar position is assumed to be the centre of this ring then almost all of the maser components fall within the inner dust shell radius, which is at ~ 5R (italics)Ï° All of the maser components fall between 1.5R (italics)Ï° and 6R (italics)Ï°. A velocity gradient with position angle was observed in the sparsely filled western region of the maser ring. If interpreted as evidence of shell rotation, this gradient implies a rotational velocity of v (italics) rot (subscirpt) sin i (italics) = 18 km.sâ »Â¹. The fractional circular and linear polarisations of the maser spots were derived from the Stokes parameter maps. The mean fractional circular polarisation of the masers components was ~ 2 percent and the median fractional linear polarisation was ~ 6 percent, with many spots displaying over ~ 30 percent linear polarisation. The mean circular polarisation implies a magnetic field of ~ 4 G in the SiO maser region if the polarisation is due to Zeeman splitting. Two maser components display a rotation of linear polarisation position angle with velocity, possibly implying a connection between the magnetic field and the velocity field variations in the region of these components.
Keywords: Very long baseline interferometry; Polarization (Light); Masers